The Implementation Analysis of Community-Based Total Sanitation Program as Strategy for Improving Clean and Healthy Living Behavior by Primary Health Care Center Workers in Grobogan Regency - Sutiyono Sutiyono; Zahroh Shaluhiyah; Cahya Tri Purnami (Jurnal Manajemen Kesehatan Indonesia, 2014)
AbstrakDi Kabupaten Grobogan, kejadian penyakit diare, campak, frambusia, dan difteri cukup tinggi. Kejadian penyakit – penyakit ini merupakan indikator PHBS masyarakat. STBM bertujuan untuk menurunkan penyakit – penyakit tersebut, namun pelaksanaan program STBM dengan indikator buang air besar sembarangan, cuci tangan pakai sabun, pengolahan air bersih, pengolahan sampah dan pengolahan limbah cair masih rendah. Penelitian ini bertujuan untuk menggambarkan pelaksanaan program STBM di Kabupaten Grobogan.Jenis penelitian adalah penelitian kualitatif dengan pendekatan fenomena. Pengumpulan data dilakukan dengan wawancara mendalam kepada 8 informan utama petugas promkes dan kesling, Focus Group Discussion dengan informan triangulasi yaitu kader, tokoh agama, tokoh masyarakat dan anggota masyarakat. Analisis data dengan content analysis.Hasil penelitian menunjukkan bahwa : sebagian besar petugas melaksanakan program STBM dengan baik. Hal yang masih kurang baik adalah kegiatan monitoring. Sebagian besar pengetahuan petugas tentang pelaksanaan program STBM sudah baik. Belum semua petugas bersikap baik dalam melaksanakan program STBM. Sebagian besar petugas belum mengetahui peraturan dalam melaksanakan program STBM tetapi kader sudah mengetahui. Semua petugas telah mendapatkan pelatihan program STBM. Semua kepala puskesmas telah melaksanakan pengawasan rutin. Sarana dan prasarana yang berupa alat pembuat jamban, sarana cuci tangan, alat pengolah sampah, lembar balik.Disarankan Dinas Kesehatan untuk meningkatkan kerjasama lintas program, lintas sektoral dalam pelaksanaan program STBM. Selain itu juga meningkatkan peran kader dalam pelaksanaan program STBM. AbstractIn Grobogan district, the occurrence of diarrhea, morbilli, framboesia, and diphtheria was relatively high. The presence of these diseases was an indicator of hygienic and healthy live behavior (PHBS) of a community. Objective of community based total sanitation (STBM) was to reduce those diseases. However, the implementation of STBM program was still inadequate. Indicators of STBM program were improper defecation, washing hand using soap, clean water management, waste management, and liquid waste management. Objective of this study was to describe the implementation of STBM program in Grobogan district.This was a qualitative study with phenomenon approach. Data collection was done by conducting in-depth interview to 8 main informants: health promotion and environmental health workers. Focus group discussion was conducted to triangulation informants; triangulation informants consisted of cadres, local religious leaders, local community leaders, and local people. Data were analyzed using content analysis method.Results of the study showed that the majority of workers implemented STBM program well. A thing that was still insufficient or inadequate was monitoring. The majority of worker’s knowledge regarding the implementation of STBM program was sufficient. Not all workers had good attitude in the implementation of STBM program. The majority of workers did not know regulations in implementing STBM program; however, cadres knew the regulation. All workers had received STBM program training. All heads of primary healthcare centers (puskesmas) had conducted routine supervision. Facilities were in the form of water closet maker instruments, hand washing facility, waste management instruments, and flip charts.Suggestions for District Health Office were to improve cross program and sector collaborations in the implementation of STBM program, to increase the role of cadres in the implementation of STBM program.